Voltage Sensor with wide Frequency Range using Deformed Helix Ferroelectric Liquid Crystal - Guo, Qi; Brodzeli, Z.; Silvestri, L.; Srivastava, A.K.; Pozhidaev, E. P.; Chigrinov, V. G.; Kwok, H. S. (Photonics Letters of Poland, 2013)
In this paper we propose a new approach to fiber optic voltage sensors via voltage-controlled Liquid Crystals (LC), which would allow direct measurement of up to 400 kV/m electric fields at multiple points. In addition, the electro-optical behavior of deformed helix ferroelectric (DHF) liquid crystal in reflective mode is described and tested. The electrically controlled reflectance has been measured at sub-kilohertz driving voltage frequency for different polarizations of the incident light. Full Text: PDF References Y.V. Izdebskaya, V.G. Shvedov, A.S. Desyatnikov, W. Krolikowski and Y.S. Kivshar, "Soliton bending and routing induced by interaction with curved surfaces in nematic liquid crystals", Opt. Lett. 35, 1692-1694 (2010). CrossRef Z. Ge, S. Gauza, M. Jiao, H. Xianyu and S.T. Wu, "Electro-optics of polymer-stabilized blue phase liquid crystal displays", Appl. Phys. Lett. 94, 101104 (2009). CrossRef Z. Brodzeli, F. Ladouceur, L. Silvestri, A. Michie, V. Chigrinov, G. Q. Guo, E. P. Pozhidaev and A. D. Kiselev, "Liquid crystal-based hydrophone arrays", APOS (2012). CrossRef T. Tanigawa, Y. Sakakibara, S. Fang, T. Sekikawa and M. Yamashita, "Spatial light modulator of 648 pixels with liquid crystal transparent from ultraviolet to near-infrared and its chirp compensation application", Opt. Lett. 34, 1696-1698 (2009). CrossRef K. H. Yang and T. C. Chieu, "Transport Properties of Ions in Ferroelectric Liquid Crystal Cells", Jpn. J. Appl. Phys. 28, 2240-2246 (1989) CrossRef I.C. Khoo and S.T. Wu, "Optics and Nonlinear Optics of Liquid Crystals", World Scientific, Singapore (1993). V.G. Chigrinov, "Liquid Crystal Devices: Physics and Applications", Artech House, Boston: London, (1999). A.D. Kiselev, E.P. Pozhidaev, V.G. Chigrinov and H.S. Kwok, "Polarization-gratings approach to deformed-helix ferroelectric liquid crystals with subwavelength pitch", Phys. Rev. E 83, 31703 (2011). CrossRef N. A. Clark and S. T. Lagerwall, "Submicrosecond bistable electro-optic switching in liquid crystals", Appl. Phys. Lett. 36, 899-901 (1980). CrossRef L.A. Beresnev, V.G. Chigrinov, D.I. Dergachev, E.P. Pozhidaev, J. Funfshilling and M. Schadt, "Deformed helix ferroelectric liquid crystal display: A new electrooptic mode in ferroelectric chiral smectic C liquid crystals", Liq. Cryst. 5, 1171-1177 (1989). CrossRef Z. Brodzeli, H.K. Bal, V.G. Chigrinov, A. Murauski, and F. Ladouceur, "Electrical energy harvesting device for current/voltage fibre-based sensors", Optical Fibre Technology (ACOFT), 2010 35th Australian Conference on Fibre Technology, 1-2, (2010). <a class="file" href="http://ieeexplore.ieee.org/xpl/articleDetails.jsp?tp=&arnumber=5929890&contentType=Conference+Publications&sortType%3Dasc_p_Sequence%26filter%3DAND%28p_IS_Number%3A5929877%29%26rowsPerPage%3D75" target="_parent">DirectLink X. Zhao, F. Boussaid, A. Bermak and V.G. Chigrinov, "High-resolution thin ?guest-host? micropolarizer arrays for visible imaging polarimetry", Opt. Exp. 19, 5565-5573 (2011). CrossRef X.H. Li, A. Murauski, A. Muravsky, P.Z. Xu, H.L. Cheung, and V. Chigrinov, "Grayscale Generation and Stabilization in Ferroelectric Liquid Crystal Display," J. Display Technol. 3, 273-279 (2007). CrossRef E.P. Pozhidaev, S. Torgova, M. Minchenko, C. Yednak, A. Strigazzi and E. Miraldi, "Phase modulation and ellipticity of the light transmitted through a smectic C* layer with short helix pitch", Liq. Cryst. 37, 1067-1081, (2010). CrossRef E.P. Pozhidaev and V.G. Chigrinov, "Bistable and multistable states in ferroelectric liquid crystals", Crystallography Reports. 51, 1030-1040 (2006). CrossRef Q. Guo, F. Fan, T. Du, and V.G. Chigrinov, "Electrooptic Response of FLC: Effect of Alignment Materials", SID’11 Conference, P-144, Los Angeles, USA, May, (2011). CrossRef G. Hegde, P. Xu, E.P. Pozhidaev, V.G. Chigrinov, and H.S. Kwok, "Electrically controlled birefringence colours in deformed helix ferroelectric liquid crystals", Liq. Cryst. 35, 1137-1144 (2008). CrossRef